Synthesis, experimental and theoretical characterization with inhibitor activity for 1,2,4-traizaol derivatives - Omer, Rebaz A.; Koparir, Pelin; Koparir, Metin (Scientific Publishers, 2022)
This study aims to synthesize and identify both theoretically and experimentally 4-phenyl-5-(thiophene-2-yl)-4H-1,2,4-triazole-3-thiol and 4-ethyl-5-(thiophene-2-yl)-4H-1,2,4-triazole-3-thiol compounds. Experimentally, FT-IR and NMR techniques have been used to characterize the synthesized compounds. The density functional theory with the basis set of cc-pVDZ have been utilized for measuring the molecular geometry, vibrational frequencies, and gauge including atomic orbital (GIAO) 1H and 13C NMR chemical shifts of the title compound in the ground state. The results have shown that the optimized geometry replicate the theoretical vibrations and the calculated chemical shift in line with the experimental values are in good harmony. B3LYP/cc-pVDZ was applied to the aforementioned compound to find different parameters such as the energy of the highest occupied and lower unoccupied molecular orbital (EHOMO and ELUMO), moreover, the bandgap energy (?E) and the dipole moment (?) are calculated for the corrosion efficacy of organic compounds whose molecular geometry and electronic properties have been previously studied. Properties such as hardness (?), softness (?), electronegativity (?) values are computed using the respective measurements to investigate the inhibitor activity of the compound. The fraction of transferred electrons (?N) is also calculated, which determined the interaction between the iron surface and the organic compounds. Corrosion inhibitor behavior can therefore be predicted without an experimental study. The findings of the calculations show good relation between organic-based corrosion inhibitors and quantum chemical parameters process. © 2022 Indian Journal of Chemistry (IJC). All right reserved.
Keywords: 4-ethyl-5-(thiophene-2-yl)-4H-1 2 4-triazole-3-thiol; 4-phenyl-5-(thiophene-2-yl)-4H-124-triazole-3-thiol; Corrosion Inhibitory Activity; Density function theory; Electronic Properties; Synthesis